Assessment of the Fingerprint Identification System and Digitization Project of The National Bureau of Investigation (NBI) Towards Automated Fingerprint Identification System (AFIS) Implementation - Portugal, Arianne Joy; Dalugdog, Wilfredo; Arayata, Govinda Dasi; Garcia, Joyce (Future Science / FSH-PH Publications, 2025)
This study aims to assess the National Bureau of Investigation’s (NBI) fingerprint identification system and provide recommendations for enhancing the ongoing fingerprint card digitization project, which is crucial for establishing an Automated Fingerprint Identification System (AFIS). The findings indicate that, while the current digitization project aligns with AFIS development, there are opportunities for improvement. One key area is the simultaneous digitization of fingerprint specimens from various government agencies to enhance efficiency. Furthermore, data analysis revealed variations in respondents’ evaluations based on years of service and job positions. Specifically, those using the manual fingerprint identification system expressed different perspectives compared to those handling digital fingerprint records, likely due to differences in procedural familiarity and operational adaptation. Most respondents acknowledged the benefits of digitization, highlighting its potential to support law enforcement in criminal prosecution and to contribute to crime reduction, the criminal justice system, and other government initiatives. Based on these findings, the study recommends that the NBI collaborate with other law enforcement agencies to ensure connectivity and minimize redundancy in fingerprint digitization. Additionally, the NBI should conduct local workshops and international seminars on AFIS to continuously improve personnel skills and system capabilities. The study recommends enhanced inter-agency collaboration, regular training programs, and the systematic integration of digitized fingerprint records to ensure the successful implementation of AFIS.